2018
DOI: 10.3390/molecules23051173
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonia tetragonioides (Pall.) Kuntze Regulates Androgen Production in a Letrozole-Induced Polycystic Ovary Syndrome Model

Abstract: Tetragonia tetragonioides (Pall.) Kuntze (TTK) is a medicinal plant traditionally used to treat various diseases such as diabetic, inflammatory, and female-related disorders. Polycystic ovary syndrome (PCOS) is a common endocrinological disorder in women of reproductive age, and hyperandrogenism is a prominent feature of PCOS resulting in anovulation and infertility. In this study, we investigated the effects of a TTK extract on androgen generation and regulation of steroidogenic enzymes in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
3
7
0
1
Order By: Relevance
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 91%
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 91%
“…Furthermore, we always test the effects at low and high concentrations of a crude extract. Natural products are administrated in dose as low as 100 to as high as 500 (35), especially for crude extracts such as CCL. Thus, we selected the lower-range concentration of 150 mg/kg/day and the higher-range concentration of 450 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…for 2 weeks, and removal of the letrozole pellet was conducted on Temporary Letrozole group rats after 2 weeks. The AF extract dose was determined according to our previous study [ 19 ]. At the end of the experiment, all rats were euthanized with isoflurane overdose.…”
Section: Methodsmentioning
confidence: 99%